MAKNA KATA YADUN PERSPEKTIF I’JAZ LUGHAWI DALAM SURAH AL FATHAYAT 10 - Mutiara Fahliza; Muhammad Hidayat Hsb, Laila Fitrah Dalimunthe, Harun Al Rasyid (CV. Adiba Aisha Amira, 2024)
This study aims to reveal the I'jaz Lughawi meaning of the sentence hands in the Qur'an surah Al-Fath, which has an I'jaz factor in the thought of diction alone used in the verse to show the meaning of power. The method used in the research is qualitative method where we review this study from various sources derived from the library (library reserch) with data collection techniques with research. The findings in this study are first, the word Yadun has the meaning of Hakiki and Majazi, Hakiki is the hand while majazi is power, second, the word ‘Yadullah’ has the meaning of Allah's power, Third, the word ‘Yadun’ has suitability in terms of qorinah with the intended target.